Why did Social and Healthcare Services Reform Fail in Finland? - Hiilamo, Heikki (Socialmedicinsk tidskrift, 2020)
Since 2005, successive Finnish governments have tried to reform the governance of social and healthcare services by transferring the responsibility for organising these services from municipalities to larger entities. So far, all attempts have failed. This study analyses why this has been the case and how expert knowledge could be used to prevent future failures.